PENERAPAN LAPORAN KEUANGAN BERDASARKAN SAK ETAP PADA BENGKEL EVRY SERVICE AC MOBIL KOTA LUBUKLINGGAU - Weli Oktaria; Eri Triharyati (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research is To apply Financial Reporting based on SAK ETAP on Evry Service Workshop of Car Air Conditioner period 2014-2016, research type is quantitative research with approach of theory, technique of data collecting in this research is using document and observation. The data analysis technique used is quantitative data. The result of the research is for the amount of Asset Evry Service Car AC Service for Rp. 451.205.000,00 thus the assets owned as a support activity activities during the accounting period. Earnings Profit obtained Evry Service Workshop AC Car for Rp. 252.280.000,00. For cash increase in Evry Service Workshop AC Car for Rp. 309.105.000,00.From the report of changes in capital Evry Service Workshop AC The car gets an additional capital from profit plus initial capital then it can be the final capital of Rp. 377.280.000,00. The application of financial reporting based on SAK ETAP in Evry Service Car Air Conditioner Service is Income Statement in 2014 amounting to Rp.251.750.000,00, 2015 Rp.228.355.000,00 and 2016 for Rp.252.280.000,00. Statement of Changes in Equity in 2014 amounting to Rp.376.750.000,00, year 2015 of Rp.353.355.000,00 and year 2016 of Rp.377.280.000,00. The balance sheet in 2014 total assets with total liabilities and equity of Rp.431.310.000,00, year 2015 amounting to Rp.450.218.000,00 and year 2016 amounting to Rp.451.205.000,00. And Cash Flow Statement in 2014 amounting to Rp.296.750.000,00 in 2015 amounting to Rp.318.355.000,00 and 2016 for Rp.309.105.000,00.Keywords: SAK-ETAP, Financial Statements